Understanding Paper-Based Documentation Practices in Medical Resuscitations to Inform the Design of Electronic Documentation Tools. Issue 8 (August 2021) - Jagannath, Swathi; Sarcevic, Aleksandra; Multak, Nina; Myers, Sage
Abstract : Objective: Despite growing use of electronic health records, many resuscitation settings still use paper-based documentation. The fast-paced and safety-critical nature of trauma and medical resuscitation environments pose challenges for real-time documentation. This study aims to understand paper-based documentation practices and inform the design of efficient electronic documentation solutions for supporting safety-critical medical processes. Methods: Data were collected through in situ observations of nurse documenters during resuscitation events and postevent interviews with nurses. These data were analyzed using frequency distribution and qualitative, open-coding techniques. Data analysis focused on the following 3 main documentation factors: temporal distribution of documentation, total number of filled out sections on the paper flow sheet across all resuscitations, and completeness of documentation per resuscitation. Results: Findings from this study highlight the time-critical nature of these settings, showing that 74% of the documentation was completed within the first 15 minutes of the resuscitation. Some sections of the paper flow sheet were filled out more than others, and a few sections were left incomplete across all events. Interviews with nurses provided insight about documentation experiences in a fast-paced environment, including variable usage of flow sheet based on nurse experience level and patient scenarios, supplemental documentation mechanisms, and information needs and preferences. Conclusions: Several design implications are discussed to inform the design of effective electronic documentation systems. Design implications focus on layout structure, prepopulating items, section placement, and completion status of the flow sheet. Future plans for research focus on combining video review with in situ observations and conducting detailed interviews with nurses to better understand their documentation experiences and preferences.